Legal Implication of Ownership in Common in Roman Private Law and Its Reception by European Jurisdictions - UTEUBAYEV, Timur T.; KIZDARBEKOVA, Antonina S. (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019, 2019)
The scientific article deals with the formation of the structure of ownership in common in Roman private law and its further reception by European jurisdictions. It explores the way the imperfect regulations that treated ownership in common as an inevitable exception in the pre-classical period of Roman law evolved into an entirely different approach in its classical period, whereby the key principles of the legal regulations on ownership in common were eventually implemented by the jurisdictions of most European countries. The wide recognition of the norms of Roman private law, which included regulations on ownership in common, affirms the universal character of the structures regulations and structures, which were developed in ancient Rome. These features are also applicable to the concept of ownership in common developed in Roman law.